Problematika slovenskega marketinškega izrazja - Šesek, Lara (Akademija MM, 2012)
The fast growth of a relatively young marketing profession in Slovenia has brought a number of linguistic problems into its terminology in the last couple of decades. The aim of this article is to highlight these issues and to discover how the profession can overcome the discrepancies in order to write a Slovenian marketing dictionary. The review of the state of the marketing terminology in Slovenia indicates two main problems: the use of different terms for the same meaning and the use of the same terms for different meanings. The main cause lies in the fact that some terms are not defined at all and that different definitions are used for the same term. This leads to misunderstanding not only in a terminological sense but also to a general misunderstanding of marketing. The lack of scientific marketing articles in Slovene and the confusion in the marketing terminology in the works of practitioners only aggravate the problem. Disagreements between faculties within and between universities on the use of terms, different naming of marketing departments and functions in companies as well as the inconsistent use of terminology by marketing related societies adds to the confusion as well.
Keywords: marketing; Slovene; slovenščina; strokovna terminologija; strokovni izrazi; terminologija; terminology; trženje